Too Early to Pick Winners: Disagreement across Experts Implies the Need to Diversify R&D Investment - Laura Diaz Anadon; Erin Baker; Valentina Bosetti; Lara Aleluia Reis (Fondazione Eni Enrico Mattei (FEEM), 2016)
Mitigating climate change will require innovation in energy technologies. Policy makers are faced with the question of how to promote this innovation, and whether to focus on a few technologies or to spread their bets. We present results on the extent to which public R&D might shape the future cost of energy technologies by 2030. We bring together three major expert elicitation efforts carried out by researchers at UMass Amherst, Harvard, and FEEM, covering nuclear, solar, Carbon Capture and Storage (CCS), bioelectricity, and biofuels. The results show experts believe that there will be decreasing returns to R&D and report median cost reductions around 20% for most of the technologies at the R&D budgets considered. Although the returns to solar and CCS R&D show some promise, the lack of consensus across studies, and the larger magnitude of the R&D investment involved in these technologies, calls for caution when defining what technologies would benefit the most from additional public R&D. Indeed, the wide divergence of opinions suggests that it is still too early to pick winners and that a broad portfolio of investments may be the best option.
Keywords: Q40; 330; R&D Investments; Energy Technology; Expert Elicitation; Risk and Reward; Low-carbon Innovation